Smart logistics in industry 5.0 - Yu, Hao (Industrial engineer) (CRC Press, 2025)
Given the importance of human centricity, resilience, and sustainability, the emerging concept of Industry 5.0 has pushed forward the research frontier of the technology-focused Industry 4.0 to a smart and harmonious socio-economic transition driven by both humans and technologies, where the role of the human in the technological transformation is predominantly focused on. Compared with Industry 4.0, smart logistics in Industry 5.0 puts more focus on the interaction between humans and technology in the digital transition with the increasing adoption of collaborative technologies, e.g., human-machine systems, collaborative robots, and human-robot collaboration.In this book, a comprehensive overview on how technological enablers will help the smart and sustainable transition of logistics planning and operations is provided. Specifically, the book focuses on the conceptual development and framework of smart logistics transformation in Industry 5.0, smart and sustainable logistics planning and operations, smart manufacturing logistics and warehousing, data-driven smart logistics and transportation, digital twin of logistics systems, and smart reverse logistics transformation. Most importantly, the role of humans in the smart logistics transformation is predominantly focused on in this book.